Status of drinking water quality and sanitation facilities in Subarnachar and Maijdee in Noakhali, Bangladesh - Barua, Tanuja; Roy, Sujit Kumar; Munna, Mehedi Hasan (Asian Journal of Medical and Biological Research, 2019)
The study was executed in Noakhali sadar (urban) and Subarnachar upazil (rural) to determine the drinking water quality and sanitation facilities. The baseline data was collected based on questionnaire survey. And the physicochemical and ionic constituents of drinking water were determined by analyzing water samples. The result showed that in rural areas about 87.5% families utilized tube-well water and the rest used polluted pond water, while in the urban areas, 91% families utilized supplied water by paying monthly. The sanitation situation in the rural area was not at satisfactory level. The mean values of several critical parameters from the two areas (rural and urban) were found to be the following. pH values were 7.10 and 7.63, respectively. Electric conductivity was found to be 530.17 and 768.76 μS/cm, respectively. Salinity value was 0.23 and 0.35 ppt, respectively. Total dissolved solid (TDS) was found to be 264.91 and 372.82 ppm, respectively. Elemental composition of the sampled water from the two areas were also obtained. Mean values of the amount of dissolved oxygen (DO) from the two areas were found to be 7.24 and 7.52 mg/l, respectively. Among the other elements, amount of phosphorus was 0.55 and 0.46 ppm, potassium was 43.82 and 35.82 mg/l, sulfate was 10.03 and 1.00 mg/l, chloride was 42.15 and 149.95 mg/l, and iron was 5.57 and 1.30 mg/l, respectively. It is clear that the drinking water quality for both areas was not good for direct consumption. The situation in the rural areas is worse than that in the urban areas. Asian J. Med. Biol. Res. March 2019, 5(1): 37-47